Quo Vadis Eksistensi Rancangan Undang-Undang Pengelolaan Ruang Udara di Indonesia - Sihaloho, Elisabeth (UI Scholars Hub, 2024)
The law draft of Air Space Management, which has been proposed by the Government since 2019, has not received clarity regarding time of ratification. The Problem of air space has become an important issue that cannot be avoided along with the rapid development of the times which makes it possible to degrade the sovereignty of a nation and state through air space. This legal research will examine the urgency of establishing the airspace management law and the positive implications or benefits obtained through the formation of this legal issue. With this type of normative juridical research, this research focuses on reviewing principles and theories which are analyzed using a statutory and regulatory approach and accompanied by literature study in data collection such as book, journal and relevant things for this research